Application of standardized project management practices in Egyptian non-profit organizations: Two case studies - Adel, Mostafa (AUC Knowledge Fountain, 2018)
A standardized project management approach across the entire organization is one of the business models adopted by non-profits that contributes to a more efficient and effective project delivery and achieving the organizations’ goals and objectives. Lack of a standardized project management approach might result in project failure and losing the skills and knowledge gained from previous projects, which significantly harms the organizational efforts to have institutional memory that allows implementing these skills and knowledge in future projects. A project management office is the key to mainstream the standardized project management methodology across non-profits. This research aims at investigating the impacts of adopting project management offices within the context of non-profits in Egypt. This study employed a qualitative approach to research through a case study methodology by interviewing key informants of two non-profits in Egypt; one national and one international, which are already implementing a project management office. The key findings of the research suggested that the two organizations under study operate in a very similar way, in terms of challenges faced by the two organizations, adopting business-like models, tendency to diversify their income generating activities and finally, adopting a project management office. The study concludes that the project management offices are the catalyst of change for non-profits to mainstream a standardized project management approach and mainstream strategies across organizations. Also, a standardized project management approach allows non-profits to implement a time-tested and results-oriented methodology of project management. Based on the lessons learned from the case studies, recommendations for non-profits are presented to guide non-profits’ executives, project management office directors, and non-profits’ staff members while implementing the PMO.